A Magnetically Recyclable Palladium-Catalyzed Formylation of Aryl Iodides with Formic Acid as CO Source: A Practical Access to Aromatic Aldehydes - You, Shengyong; Zhang, Rongli; Cai, Mingzhong (Synthesis, 2021)
A magnetically recyclable palladium-catalyzed formylation of aryl iodides under CO gas-free conditions has been developed by using a bidentate phosphine ligand-modified magnetic nanoparticles-anchored palladium(II) complex [2P-Fe3O4@SiO2-Pd(OAc)2] as catalyst, yielding a wide variety of aromatic aldehydes in moderate to excellent yields. Here, formic acid was employed as both the CO source and the hydrogen donor with iodine and PPh3 as the activators. This immobilized palladium catalyst can be obtained via a simple preparative procedure and can be facilely recovered simply by using an external magnetic field, and reused at least 9 times without any apparent loss of catalytic activity.
Keywords: formylation; palladium; magnetic nanoparticles; heterogeneous catalysis; aromatic aldehyde